PEMANFAATAN LIMBAH BOTOL PLASTIK UNTUK DIJADIKAN PRODUK AKSESORIS FESYEN - Najib, Ulfah Rizki Istiqomah Firdaus (ATRAT: Jurnal Seni Rupa, 2021)
In this globalization age, the dependence of the world community on plastic is increasing, one of which is the interest in drinks in plastic bottles. This can lead to additional waste buildup. So far, plastic bottle waste has been made into handicraft products by the community but, development process is still simple. Seeing this, the authors are interested in making plastic bottle waste as a fashion accessory product by utilizing various innovations in the development process. This design involves an experimental process with the heating method of plastic bottle waste using heat-generating devices such as an iron and a toaster. Based on the experimental results, plastic bottle waste heated using an iron visually produces a skin-like texture. The results of the experimental process have the potential to be developed into fashion accessories in the form of handbags. By holding this experiment, it is hoped that it can inspire many people. Keywords: plastic, plastic bottle waste, experiment, accessories ------------------------------------------------------------------------------------------ Di era globalisasi seperti saat ini tingkat ketergantungan masyarakat dunia terhadap plastik semakin meningkat salah satunya minat terhadap minuman berkemasan botol plastik. Hal ini dapat menyebabkan penambahan penumpukan sampah. Sejauh ini limbah botol plastik telah dijadikan produk kerajinan oleh masayarkat namun, pengembangannya masih sederhana. Berdasarkan hal tersebut penulis tertarik untuk menjadikan limbah botol plastik sebagai produk aksesoris fesyen. Perancangan ini melibatkan proses eksperimen dengan metode heating pada limbah botol plastik dengan menggunakan alat yang dapat menghasilkan panas seperti setrika dan pemanggang roti. Berdasarkan hasil eksperimen, limbah botol plastik yang di panaskan menggunakan setrika secara visual menghasilkan tekstur seperti tekstur kulit, maka dari itu hasil dari proses eksperimen memiliki potensi untuk dikembangkan menjadi produk aksesoris fesyen berupa handbag. Dengan diadakannya eksperimen ini diharapkan dapat menginspirasi banyak orang. Kata Kunci: plastik, sampah botol plastik, eksperimen, aksesoris